Comparison of the analgesic effects of liposomal bupivacaine in ultrasound-guided erector spinae plane block and surgeon-administered intercostal nerve block following video-assisted thoracoscopic lung resection: protocol for a randomized controlled trial - Yan, Jing; Feng, Yu-shu; Zheng, Xiao-yan; Zhang, Yang; Liu, Hua-yue; Yang, Yu-fan; Wan, Jing-jie; Peng, Ke; Liu, Hong; Ji, Fu-hai; Shan, Xi-sheng (Frontiers in Medicine, 2025)
BackgroundThe analgesic efficacy of liposomal bupivacaine (LB) for ultrasound-guided erector spinae plane block (ESPB) and thoracoscopic intercostal nerve block (ICNB) in thoracic surgery remains uncertain. This study aims to evaluate the analgesic efficacy of anesthesiologist-performed ESPB using LB versus surgeon-administrated ICNB with LB in patients undergoing video-assisted thoracoscopic surgery (VATS) lung resection.MethodsThis single-center, prospective, randomized, double-blinded trial will include 120 adult patients scheduled for VATS lung resection. Patients will be randomly assigned 1:1 to the ESPB group or ICNB group. Each patient will receive either an ESPB or ICNB at the end of the surgery, along with patients-controlled intravenous analgesia (PCIA) as part of a postoperative multimodal analgesia. The primary outcome is the average numeric rating scale (NRS) pain scores at rest over 72 h postoperatively (average of three 24-h time points: 24, 48, and 72 h). Secondary outcomes include NRS pain scores at rest and during activity at 24, 48, and 72 h postoperatively, Quality of Recovery 15 scores at 24, 48, and 72 h postoperatively, time to first press on the PCIA device, total opioid consumption within 72 h postoperatively, time to initiate independent bedside mobilization, length of postoperative hospital stay, and the incidence of chronic pain (defined as an NRS score ≥ 1) at 3 months post-surgery. Analyses will be performed in the modified intention-to-treat population.DiscussionWe hypothesize that anesthesiologist-performed ultrasound-guided ESPB with liposomal bupivacaine will result in lower average numeric rating scale pain scores over 72 h compared to surgeon-administrated thoracoscopic ICNB in patients undergoing VATS lung resection. The findings of this study aim to provide evidence to optimize postoperative analgesic regimens for patients undergoing VATS lung resection.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2400092927.